Scientific production on indoor air quality of environments used for physical exercise and sports practice: Bibliometric analysis - Coimbra D.R.* (2017)
© 2017 Elsevier LtdIntroduction In order to minimize adverse health effects and increase the benefits of physical activity, it is important to systematize indoor air quality study in environments used for physical exercise and sports. Objectives To investigate and analyze the scientific production related to indoor air quality of environments used for physical exercise and sports practice through a bibliometric analysis. Methods The databases Scielo, Science Direct, Scopus, Lilacs, Medline via Pubmed, and SportDiscus were searched from their inception to March 2016. Bibliometric analysis was performed for authors, institutions, countries, and collaborative networks, in relation to publication year, theme, citation network, funding agency, and analysis of titles and keywords of publications. Country, area, and impact factor of the journals were analyzed. Results Of 1281 studies screened, 34 satisfied the inclusion criteria. The first publication occurred in 1975. An increase in publications was observed in the last 15 years. Most of the studies were performed by researchers in the USA, followed by Portugal and Italy. Seventeen different scientific journals have published studies on the subject, and most are in the area of Environmental Sciences. It was noted that the categories of author keywords associated with “Pollutants,” “Sport Environment,” and “Physical Exercise” were the most commonly used in most studies. A total of 68% of the studies had at least one funding agency, and 81% of studies published in the last decade had funding. Conclusions Our results demonstrate that there is recent exponential growth, driven in the last decade by researchers in environmental science from European institutions.